Entrepreneurial Orientation Studies on Food And Beverage MSMEs To Examine The Effects of Social Media Marketing and Digital Content Marketing Activity on Business Performance - Aryani, Dwi Retno; Tuti, Meylani (School of Business, IPB University (SB-IPB), 2023)
The Indonesian government is encouraging the MSME sector to go digital following recent technological advancements to optimize its potential and productivity. The purpose of this study is to ascertain the impact of social media marketing (SMM) and digital content marketing activities (DCMAs) on entrepreneurial orientation (EO) and business performance (BP) of micro, small and medium enterprises (MSMEs) in the food and beverage industry. Entrepreneurs in the food and beverage industries who are located in the JABODETABEK area have used social media and prepared digital content as a marketing tool to make up the study's demographic. This study used a quantitative method with 272 MSME respondents who had responded to statements in the online questionnaire, which were collected over two months. SEM (Structural Equation Modeling), a data analysis technique, was employed with Lisrel 12. The findings demonstrated that Entrepreneurial Orientation and Business Performance are stronger directly influenced by digital marketing content activities than the influence of social media marketing. In addition, Entrepreneurial Orientation also affects Business Performance. This research found that MSMEs in the food and beverage industry may focus on developing DCMAs and building an entrepreneurial mindset in recognizing the desires of modern customers in shifting marketing to be more digital-based to improve its business performance Keywords: social media marketing (SMM), digital content marketing activity (DCMA’s), entrepreneurial orientation (EO), business performance (BP), food and beverage MSME